Revitalization of Socio-Cultural Based Dolanan in the Formation of Children's Character in Javanese Families in Binjai, Indonesia - Purba, Nelvitia; Ovami, Debby Chyntia; Kamaruddin, Mohd Khairul Amri; Hayati, Winta; Novita, Tri Reni (El-Usrah: Jurnal Hukum Keluarga, 2024)
Traditional games or children's games are currently threatened with extinction because they are being displaced by the onslaught of modern culture which is more accepted by children. This research uses a mixed descriptive qualitative and quantitative research method analyzed with the theory of structural functionalism. There are three data collection techniques in research, namely interviews, documentation and questionnaires. The research results show that: The existence of Javanese dolanan oral traditions, among others; Traditional expressions, pennyandra, sesanti puja, Wangsalan, cangkriman, Parikan, Tembang gede, macapat, Tembang dolanan, Javanese style, spiritual songs, fairy tales, folk history, humor stories and folk drama: Jemblong, ketoprak, ludruk, wayang, ande-ande, the most popular Javanese dolanan and wayang songs are performed such as: weddings and religious and national holidays. The revitalization of the Javanese dolanan oral tradition for the formation of children's character in the family environment of the Pujakesuma community of Binjai city must be carried out considering that foreign culture has a very big influence on the character of the younger generation because the Javanese dolanan oral tradition is a cultural asset of the nation so it needs to be maintained in the formation of children's character in the current family environment. through the support of facilities and infrastructure, cooperation, socialization and communication. In this context, according to the social theory of structural functionalism, the family has an influence in instilling character values in children whose existence needs to be maintained and preserved.